Sexual Violence, Condom Negotiation, and Condom Use in the Context of Sex Work: Results From Two West African Countries. (1st March 2015) - Wirtz, Andrea L.; Schwartz, Sheree; Ketende, Sosthenes; Anato, Simplice; Nadedjo, Felicity D.; Ouedraogo, Henri G.; Ky-Zerbo, Odette; Pitche, Vincent; Grosso, Ashley; Papworth, Erin; Baral, Stefan
Abstract : Background: Female sex workers (FSWs) are vulnerable to violence within and beyond the workplace. Violence is associated with increased burden of HIV, possibly explained through physiologic or behavioral causal pathways. These analyses sought to determine the relationship between lifetime sexual violence with unprotected, condomless vaginal intercourse (UVI) among FSWs in West Africa. Methods: FSWs (aged ≥18 years) were recruited into a cross-sectional study through respondent-driven sampling in two West African countries, Togo and Burkina Faso. A total of 1380 participants were enrolled from January to July 2013, and completed a sociobehavioral questionnaire and HIV testing. Measures included sex work history, lifetime experiences of violence victimization, sexual practices, and UVI (past month). Crude and adjusted robust log binomial regression was conducted to estimate prevalence ratios (PrR) as a measure of association between UVI with clients and the primary exposure, forced sex. Results: Self-reported lifetime physical abuse (47.3%), forced sex (33.0%), and any violence (57.9%) were common. Almost one-quarter (23.9%) reported recent UVI with clients. History of forced sex was independently associated with recent UVI with clients [vs. none, adjusted PrR: 1.49; 95% confidence interval (CI): 1.18 to 1.88], with evidence of partial mediation by difficult condom negotiation with regular (aPrR: 1.83; 95% CI: 1.43 to 2.34) and new clients (aPrR: 1.60; 95% CI: 1.13 to 2.29). Discussion: These data demonstrate the significant relationship between sexual violence experienced by FSWs and unprotected sex with clients. Comprehensive interventions reducing vulnerabilities to violence combined with improved condom negotiation are needed to address the complex influences of condom use during sex work as a means of ultimately lowering HIV acquisition and transmission.